Coming a long way: Switzerland's transformation from a majoritarian to a consensus democracy (1848–2018). Issue 6 (17th August 2020) - Vatter, Adrian; Freiburghaus, Rahel; Arens, Alexander
ABSTRACT: How did relevant key events shape the long-term transformation of Swiss democracy in terms of horizontal and vertical power-sharing? And why did existing systems, that is "role models", inspire this transformation? Renowned for being one of the oldest democracies in Europe, Switzerland offers a unique, case-based research opportunity to scrutinize the evolutionary process of democratization. We argue that Lijphart's seminal "consensus-versus-majoritarian"-democracy model constitutes a suitable tool to study the long-term evolution of democracies. In order to make it applicable across time, however, conceptual pitfalls need to be tackled. The conceptual part is thus concerned with the problem of identifying relevant time periods. Empirically, Switzerland's 170 years of democratic change are analysed based on Lijphart's framework. Moreover, mechanisms of transnational diffusion that explain why "role models" (the United States, the Weimar Republic, and the Netherlands) inspired the transformation of Swiss democracy are explored. The analysis draws on new, historic data going as far back as the late eighteenth and early nineteenth century. The longitudinal design reveals a long-term transformation of Switzerland from an almost purely majoritarian democracy to post-war "paradigmatic consensualism". The article thereby offers new insights into how changes in the formal-institutional setting are related to the paradox of democratization.